SUNN PEST SPECIES AND ITS HIBER NATION SITES IN DIYALA GOVERNORATE / IRAQ - & Al-Jorany, Shblawy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This study was conducted in Diyala governorate/Iraq during wintering period of the sunn pest from Dece. 2016 to Feb. 2017. Three species of sunn pest was diagnostic. These species are Eurygaster integriceps (Puoton, 1881), E. testudinaria (Geoffory, 1785) and E .maura (len.1758).E .maura was new species recorded to Iraq funna .E. integriceps is The most abundance of the three species hibernated in the fields of the four region of Diyala governorate. The results showed that the three species of genus Eurygaster which diagnostic in Diyala governorate were overwintered as an adults under bushes ,dead leaves, weed ,date palm leaf base .The heights total number of adults(68,56,51 and 44adults/5m2) was found under cogon grass(Imperata cylindrican L.), Bermuda grass(Cyndo dactylon L.),Grape tree(Vitis vinifera L.)and Eucalyptus tree(Eucalyptus spp.) respectively. Higher densities were recorded in Muqdadiyah (200), Balad rooz (193), Kalas (113) and decreased to( 65) adults in Khanakin. Found that the higher percentage for species E. integriceps then followed E. testudinaria finally the species E. maura in all region in Diyala governorate.